USE OF ONLINE RESOURCES IN THE PROCESS OF STUDYING UKRAINIAN LITERATURE IN THE 6TH GRADE OF NUSH - Кириленко, Надія; Марченко, Єлизавета (SWorldJournal, 2026)
The article considers new approaches to the study of Ukrainian literature in the 6th grade of the New Ukrainian School, in particular the use of online resources (Kahoot, Padlet, LearningApps, electron ic libraries). which makes the study of literature dy